Plastitch tailor enterprise – FS varsity jacket/ Nur Fazira Mohd Fauzi ... [et al.] - Nur Fazira, Mohd Fauzi; Nurzaina, Nizamudin; Aizuddin Asif, Farizal; Muhammad Raif Shamil, Rosly; Abdul Hallim, Zainulizam (2019)
Plastitch Tailor Enterprise is based on partnership that consists of five (5) members which hold important positions in the business such as General Manager, Marketing Manager, Operational Manager and Financial Manager. Each members contribute the amount of RM20,000.00 and the total amount of the business capital is RM100,000.00. Plastitch Tailor Enterprise offers a four season varsity jacket. This jacket can be worn at any seasons as the product is made out of plastic that can adapt to hot and cold weather. It can be worn during hot weather as the jacket can prevent direct sunlight from hitting the wearer. It can also can be worn during cold weather as it can be worn as an outer layer of the inner layer. Plastitch Tailor’s target market is mainly for adults and teenagers but we also provide a kind of service where we make customized jacket based on customers’ orders. This kind of service can attract more customer as the jacket has no fixed cutting. It can be altered according to customers’ body shapes. The location of our premise is located in Denai Alam, Shah Alam. The reason why we chose this location is because the population in Denai Alam is 32,000. with high population can increase the possibility of customers to come to our shop which can also increase our sales. The area is also full of shops that sells clothing. Basically, this area is famous for clothing shopping so it also can attract many customers that are searching for brand new design.